Our own books! - Lau, Paul Ngee Kiong; Ng, Kui Choo; Wee, Cindy; Kuan, Stephanie; Sim, Jaqueline; Sim, Linda (UiTM Sarawak, 2004)
Two books written by UiTMCS lecturers were launched by the Honourable Chief Minister of Sarawak, YAB Pehin Sri Dr. Haji Abdul Taib Mahmud on 22 May 2004 in Bintulu during the Teacher's Day Celebration.